The administration of criminal justice at the Cape of Good Hope, 1795-1828 - Fine, Hilton (1991)
Includes bibliography.The administration of justice at the Cape cannot be seen separately from the substantive law which was applied during the period 1795 to 1828. Therefore, in order to actualise the administrative of criminal justice during this period, the sources of criminal law are considered and their significance for the administration of justice are explained